Microvillus inclusion disease: a subtotal enterectomy as a bridge to transplantation. Issue 6 (1st November 2016) - van Hoeve, Karen; Hoffman, Ilse; Fusaro, Fabio; Pirenne, Jacques; Vander Auwera, Ann; Dieltjens, Anne-Marie; De Hertogh, Gert; Monbaliu, Diethard; Miserez, Marc
Abstract: Background: Microvillus inclusion disease (MVID) is a known congenital cause of intractable diarrhea resulting in permanent intestinal failure. There is need for a lifelong total parenteral nutrition (TPN) from diagnosis and the prognosis is poor. Most patients die by the second decade of life as a result of complications of parenteral alimentation including liver failure or sepsis. The only available treatment at this moment is a small bowel transplantation. But before that moment, the patients often suffer from a persistent failure to thrive and electrolyte disturbances despite continuous TPN. Methods and Results: We report what we believe is a first case of an extensive small bowel resection in a 5-month-old boy with proven MVID to act as a bridge to (liver-) intestinal transplantation to treat failure to thrive and intractable diarrhea. Conclusions: An extensive small bowel resection can be done to enhance the chance of survival leading up to the transplantation by managing fluid and electrolyte imbalance. It facilitates medical management of these patients and makes a bowel transplantation possible at a later stage.